Building Customer Satisfaction Through Promotion And Service Quality To Gojek Service Users In Medan - Asrizal Efendy Nasution; Imam Syahputra (Journal of International Conference Proceedings (JICP), 2022)
This study aims to determine and analyze the effect of promotion and service quality on customer satisfaction of Gojek service users in Medan. The population in this study were all economic and business students at the University of Muhammadiyah Sumatra Utara. Sampling used a purposive sampling technique with an accidental sampling approach, namely anyone who coincidentally met and had used the services of Gojek more than 2 times with a total sample of 100 respondents. The data analysis technique used multiple linear regression analysis, partial and simultaneous hypothesis testing and the coefficient of determination. The results showed that the variables of promotion and service quality, either partially or simultaneously, had a positive and significant influence on customer satisfaction using Gojek services for students of the Faculty of Economics and Business, University of Muhammadiyah Sumatera Utara Medan. Keywords: Promotion, Service Quality, Customer Satisfaction